2017
DOI: 10.1051/0004-6361/201730411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an eccentric inner Jupiter on the dynamical evolution of icy body reservoirs in a planetary scattering scenario

Abstract: Aims. We analyze the dynamics of small body reservoirs under the effects of an eccentric inner giant planet resulting from a planetary scattering event around a 0.5 M ⊙ star. Methods. First, we used a semi-analytical model to define the properties of the protoplanetary disk that lead to the formation of three Jupiter-mass planets. Then, we carried out N-body simulations assuming that the planets are close to their stability limit together with an outer planetesimal disk. In particular, the present work focused… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 67 publications
5
34
0
Order By: Relevance
“…Greenstreet et al (2012) suggested that the EKM of Jupiter can produce retrograde near-Earth asteroids such as 2009 HC82, and most of the test particles are near the 3/1 resonance with Jupiter at the instant when they flip to the retrograde state. Zanardi et al (2017) and Naoz et al (2017) suggested that orbits of the outer test particles can also flip from prograde to retrograde or vice versa in the presence of an inner eccentric planet. They discussed the production of debris disk particles by an eccentric Jupiter-mass planet.…”
Section: Production Of Retrograde Centaursmentioning
confidence: 99%
See 1 more Smart Citation
“…Greenstreet et al (2012) suggested that the EKM of Jupiter can produce retrograde near-Earth asteroids such as 2009 HC82, and most of the test particles are near the 3/1 resonance with Jupiter at the instant when they flip to the retrograde state. Zanardi et al (2017) and Naoz et al (2017) suggested that orbits of the outer test particles can also flip from prograde to retrograde or vice versa in the presence of an inner eccentric planet. They discussed the production of debris disk particles by an eccentric Jupiter-mass planet.…”
Section: Production Of Retrograde Centaursmentioning
confidence: 99%
“…Namouni & Morais (2018a) suggested based on numerical experiments that 2015 BZ509 has an interstellar origins. In recent years, it is found that particles in prograde orbits can flip to retrograde state and back again due to the eccentric Kozai mechanism (EKM) of giant planets (Lithwick & Naoz 2011;Naoz 2016;Naoz et al 2017;Zanardi et al 2017). Greenstreet et al (2012) adopted this EKM of Jupiter to discuss the production of the only one retrograde near-Earth asteroid (NEA) 2009 HC82.…”
Section: Introductionmentioning
confidence: 99%
“…Higher order resonances can further excite test particle eccentricity and inclination. This has important implications for the dynamical evolution of debris disk surrounding planets in eccentric orbits (e.g., Zanardi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For the particular case where the outer body is a massless test particle, Farago & Laskar (2010) obtained results consistent with those derived by Ziglin (1975). Recently, Naoz et al (2017) and Zanardi et al (2017) (hereafter Paper 1) carried out two complementary works aimed at analyzing the dynamical evolution of outer test particles under the effects of an eccentric inner massive perturber. In fact, Naoz et al (2017) studied the secular evolution of a far away test particle orbiting an inner massive binary up to the octupole level of approximation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Naoz et al (2017) showed that secular interactions up to the octupole level lead to variations of the test particle's eccentricity and introduces higher-level resonances, which may produce chaos. In this context, Zanardi et al (2017) made use of N-body simulations and analyzed the dynamical evolution of outer test particles in presence of an eccentric inner Jupiter-mass planet resulting from a planet-planet scattering event around a 0.5 M ⊙ star. The results derived by these authors suggest that planetary scattering scenarios lead to an efficient production of outer small body reservoirs composed of particles with prograde and retrograde inclinations, and other ones whose orbit flips from prograde to retrograde and back again in their evolution.…”
Section: Introductionmentioning
confidence: 99%